Aerosolization behavior of prokaryotes and fungi during composting of vegetable waste. (15th April 2019) - He, Pinjing; Wei, Shunyan; Shao, Liming; Lü, Fan
Highlights: Bioaerosol samples were collected from a 30 t-waste/d composting facility. Preferential aerosolization behavior of bacteria, archaea and fungi was analyzed. Low-abundant microorganisms such as Thaumarchaeota also preferentially aerosolized. More than 90% of aerosolized microbial genera were pathogenic. Abstract: Aerobic composting is one of the most effective ways to treat biowaste. However, microorganisms, including prokaryotes (i.e. bacteria and archaea) and fungi, are inevitably released from the compost as bioaerosols during biowaste composting. The release pattern of bioaerosols was analyzed during vegetable waste composting through onsite direct sampling of bioaerosol, compost on the pile surface, and compost inside the windrows to have a systematic understanding of the aerosolization behavior of bacteria, archaea, and fungi during composting. A total of six and three dominant microbial phyla were detected in the vegetable compost and aerosol, respectively. The overall aerosolization index of archaea and bacteria was 0–79 and 0–214, respectively, while that of fungi ranged from 0 to 397. The major preferentially aerosolized microorganism phyla included Bacteroidetes (bacteria) and Basidiomycota (fungi). Furthermore, the aerosolization index of bacterial and fungal genera was 0–22, 500 and 0–9000, respectively. Seven major preferentially aerosolized bacterial genera, including Brevundimonas, Massilia, Chryseobacterium, Chryseobacterium, Kurthia, Burkholderia-Paraburkholderia, and Acinetobacter were detected with aerosolization indices of 171, 491, 1478, 22, 460, 5525, 4014, and 631, respectively. With regard to fungal genera, Cochliobolus, Sclerotinia, and Aspergillus were noted to get easily aerosolized, with maximum aerosolization indices of 7344, 8582, and 439, respectively. The microbial number in the aerosol from composts ranged from 400 to 4800 cell/m 3 . Besides, more than 90% of easily aerosolized microbial genera were Gram-negative and pathogenic. Thus, the microorganisms released from vegetable compost may have certain detrimental effect on human health.